2013
DOI: 10.1038/onc.2013.146
|View full text |Cite
|
Sign up to set email alerts
|

Dual roles of hemidesmosomal proteins in the pancreatic epithelium: the phosphoinositide 3-kinase decides

Abstract: Given the failure of chemo- and biotherapies to fight advanced pancreatic cancer, one major challenge is to identify critical events that initiate invasion. One priming step in epithelia carcinogenesis is the disruption of epithelial cell anchorage to the basement membrane which can be provided by hemidesmosomes (HDs). However, the existence of HDs in pancreatic ductal epithelium and their role in carcinogenesis remain unexplored. HDs have been explored in normal and cancer pancreatic cells, and patient sample… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 25 publications
0
37
0
Order By: Relevance
“…In an experimental BP180 humanized mouse model, skin fragility was induced by passive transfer of F(ab′) 2 fragments, and in C3‐deficient mice, blister formation could be induced by passive transfer of anti‐BP180 antibodies from patients with BP . Another complement‐independent mechanism of disruption of the hemidesmosome has been described in pancreatic ductal adenocarcinoma, in which cleavage of the extracellular domain of BP180 by MMP‐9 has been shown to be dependent on the phosphoinositide 3‐kinase pathway …”
Section: Laboratory Results For Patients With and Without C3mentioning
confidence: 99%
“…In an experimental BP180 humanized mouse model, skin fragility was induced by passive transfer of F(ab′) 2 fragments, and in C3‐deficient mice, blister formation could be induced by passive transfer of anti‐BP180 antibodies from patients with BP . Another complement‐independent mechanism of disruption of the hemidesmosome has been described in pancreatic ductal adenocarcinoma, in which cleavage of the extracellular domain of BP180 by MMP‐9 has been shown to be dependent on the phosphoinositide 3‐kinase pathway …”
Section: Laboratory Results For Patients With and Without C3mentioning
confidence: 99%
“…The activation of PTEN/PI3K/AKT signaling by hepatitis B X‐interacting protein (HBXIP) subsequently boosted S100A4 expression in breast cancer cells . Inhibiting PI3K in BxPC‐3 pancreatic cancer cells also abrogates S100A4 expression . Inhibition of Akt by Akti, effectively blocks α6β4‐dependent S100A4 expression .…”
Section: Discussionmentioning
confidence: 99%
“…These findings are consistent with the concept that altering the endogenous sst2 brake may confer an advantage for Our previous data demonstrated that sst2 expression in pancreatic cancer cells inhibits their tumorigenicity / invasion, with those sst2 tumor suppressive functions relying on PI3K inhibition. [11][12][13] Mechanistically, somatostatin-activated sst2 inhibits PI3K activity by disrupting a pre-existing complex comprising the sst2 receptor and the p85 PI3K regulatory subunit which directly interact.…”
Section: Discussionmentioning
confidence: 99%
“…10 Importantly, inhibition of phosphoinositide 3-kinase (PI3K) and of nuclear factor-κB (NF-κB) underlies sst2 tumor suppressive activity in pancreatic cancer cells. [11][12][13] Activation of PI3K activity is required for Kras-initiated carcinogenesis and maintenance, and high PI3K activity is observed in nearly all PDAC. [14][15][16] Yet, no mutation has been found in PI3K itself or any regulatory genes which could explain the high activation of PI3K generally observed in PDAC.…”
Section: Introductionmentioning
confidence: 99%